2014
DOI: 10.3389/fnsys.2014.00162
|View full text |Cite
|
Sign up to set email alerts
|

Developmental hearing loss impairs signal detection in noise: putative central mechanisms

Abstract: Listeners with hearing loss have difficulty processing sounds in noisy environments. This is most noticeable for speech perception, but is reflected in a basic auditory processing task: detecting a tonal signal in a noise background, i.e., simultaneous masking. It is unresolved whether the mechanisms underlying simultaneous masking arise from the auditory periphery or from the central auditory system. Poor detection in listeners with sensorineural hearing loss (SNHL) is attributed to cochlear hair cell damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 90 publications
3
19
0
Order By: Relevance
“…To induce CHL in experimental animals, several approaches have been used. Beside plugging the auditory canal [14][15][16] or filling the middle ear cavity using poloxamer 22 , CHL was also induced by malleus removal 11,21,[39][40][41] as in the present study. In previous studies the effectivity of an experimental induced CHL was typically examined by measuring auditory brainstem responses (ABRs) which massively decreased to all delivered sound intensities and frequencies after this intervention 14,16 .…”
Section: Discussionsupporting
confidence: 49%
“…To induce CHL in experimental animals, several approaches have been used. Beside plugging the auditory canal [14][15][16] or filling the middle ear cavity using poloxamer 22 , CHL was also induced by malleus removal 11,21,[39][40][41] as in the present study. In previous studies the effectivity of an experimental induced CHL was typically examined by measuring auditory brainstem responses (ABRs) which massively decreased to all delivered sound intensities and frequencies after this intervention 14,16 .…”
Section: Discussionsupporting
confidence: 49%
“…Smith and Zwislocki, 1975; Smith, 1979; Westerman and Smith, 1984), and is a nonlinearity that can only be explained by processes beyond the auditory nerve. Recent studies in animal models show cortical responses that are suggestive of overshoot (Gay et al 2014). Some previous studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of abnormal sound input early in life that could potentially lead to longer-term listening difficulties is temporary unilateral conductive loss due to infection of the middle ear, a condition named amblyaudia in analogy to the better known amblyopia ( Whitton & Polley 2011 ; Kaplan et al 2016 ). Animal studies have shown that short periods of such conductive loss can alter CANS development and disrupt binaural integration and hearing in noise even after a complete reversal of the loss ( Knudsen et al 1984 ; Popescu & Polley 2010 ; Polley et al 2013 ; Gay et al 2014 ). While some residual conductive loss sometimes remains in older children and adults with a history of middle ear infection, especially those who required multiple intubations (typically 5 to 10 dB, especially above 4 kHz; Hunter et al 1996 ), the bulk of the lingering difficulties hearing in noise is likely the result of impaired binaural hearing, as evidenced by poor performance on the masking level difference test ( Lynn et al 1981 ), for example ( Teele et al 1984 ; Pillsbury et al 1991 ; Wilmington et al 1994 ; Hall et al 1995 ; Hogan & Moore 2003 ; Gray et al 2009 ).…”
Section: Hidden Hearing Lossmentioning
confidence: 99%